Do ICT Development and labor force foster Economic Growth in Indonesia? - Siti Mudrikah; Muhammad Fathrul Quddus (Universitas Wahid Hasyim Semarang, 2023)
Purpose: This paper aims to determine the ICT Development Index and other supporting variables affecting Indonesia's economic growth.Methods: This study uses secondary data from 1996-2019. Using economic growth variables as endogenous variables, and labor force, gross fixed capital formation (GFCF), cellular phones per 100 people, fixed telephones per 100 people, and internet users as exogenous variables. The data analysis technique used OLS multiple linear regression with eviews 9 application.Finding: The neoclassical theory developed by Solow (1957) a name